A new species of Sparsorythus Sroka & Soldán, 2008 (Ephemeroptera: Tricorythidae) from Eastern Ghats of Southern India - Sivaruban, T; Srinivasan, Pandiarajan; Barathy, S; Rosi, M Bernath; Isack, Rajasekaran (Zootaxa, 2021)
A new mayfly species, Sparsorythus sivaramakrishnani sp. nov. from the stream of Pullian cholai, Thuraiyur, Namakkal district, Tamil Nadu, India is described based on male and female nymphs. Sparsorythus sivaramakrishnani sp. nov. differs from the closely related S. gracilis by the shape of the left prostheca, the number of bristle-like processes at base of left prostheca, the ratio and shape of right prostheca, the ratio of femur length: width, the size of the female nymph, the mesonotum overlapping in fifth abdominal segment of the female, and by the shape of hypopharyngeal lingua.